FORMING THE ECONOMIC SECURITY POTENTIAL OF A MULTI-SECTORAL CORPORATION - M. A. Gureyeva (Russian Journal of Economics and Law, 2012)
The article views the features of formation of economic security potential in a multi-sectoral corporation. The author presents the results of analysis of economic security potential in a multi-sectoral corporation compared with the features of economic security provision in an enterprise.